Respuesta :

a. x² - y² = (x + y)(x - y)

b. x⁶ - y⁶ = [(x - y)(x² + xy + y²)][(x + y)(x² - xy + y²)]

The problem has to do with simplification

What is simplification?

Simplification is the reduction of an expression into a simpler form

a. How to Simplify x² - y²

To simplify x² - y², we see that it is the difference of two squares.

So, x² - y² = (x + y)(x - y)

Thus, x² - y² = (x + y)(x - y)

b. How to simplify x⁶ - y⁶

To simplify x⁶ - y⁶, we re-wrire it in the form of difference of two squares.

So, x⁶ - y⁶ = (x³)² - (y³)²

= (x³ - y³)(x³ + y³)

Now (x³ - y³) is the difference of two cubes.

So, (x³ - y³) = (x - y)(x² + xy + y²)

Also,  (x³ + y³) is the sum of two cubes.

So, (x³ + y³) = (x + y)(x² - xy + y²)

So, x⁶ - y⁶ = (x³)² - (y³)²

= (x³ - y³)(x³ + y³)

= [(x - y)(x² + xy + y²)][(x + y)(x² - xy + y²)]

So, x⁶ - y⁶ = [(x - y)(x² + xy + y²)][(x + y)(x² - xy + y²)]

Learn more about simplification here:

https://brainly.com/question/28060764

#SPJ1

ACCESS MORE